Influence of pyridine treatment on the optical properties of organic-inorganic perovskite films - Mahon, Natallia S.; Zelenyak, Tatyana Y.; Korolik, Olga V.; Gladyshev, Pavel P.; Mazanik, Alexander V. (Journal of the Belarusian State University. Physics, 2019)
The pyridine treated films of organic-inorganic perovskites with CH3NH3PbI3 and CH3NH3Pb(I0,57Cl0,43)3 composition were studied. An analysis of the transmission and photoluminescence spectra, as well as kinetics of photoluminescence band intensity and mass center under continuous illumination showed that the effect of pyridine on organic-inorganic perovskites is ambiguous, because along with photostabilization (decrease in the rate of change of photoluminescence band parameters under illumination), the substantial decrease of dark stability takes place, which manifests itself in the change of phase composition during storage.
Keywords: photovoltaics; organic-inorganic perovskites; photostability; pyridine; confocal spectroscopy